2017
DOI: 10.1111/1346-8138.13748
|View full text |Cite
|
Sign up to set email alerts
|

Initial study of transdermal oxybutynin for treating hyperhidrosis

Abstract: Oral oxybutynin for treating hyperhidrosis is effective and safe. Its side-effects are mild but frequent so we consider whether transdermal oxybutynin (considered to have a better side-effect profile) could be an alternative for treating hyperhidrosis. During 2015, a prospective study was conducted. Epidemiological variables, effectiveness (using the Hyperhidrosis Disease Severity Scale) and tolerance to transdermal oxybutynin were compiled concerning two different groups (patients previously treated or untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…However, transdermal oxybutynin showed effectiveness only in patients who had not received systemic drugs, but this response was of short duration (<12 months). 84 The contribution of this approach, although currently of limited value, is not yet possible to interpret.…”
Section: Emerging Therapies Of Palmar Hyperhidrosismentioning
confidence: 99%
“…However, transdermal oxybutynin showed effectiveness only in patients who had not received systemic drugs, but this response was of short duration (<12 months). 84 The contribution of this approach, although currently of limited value, is not yet possible to interpret.…”
Section: Emerging Therapies Of Palmar Hyperhidrosismentioning
confidence: 99%
“…Both the OC gel 3% by Nguyen et al 6 and the OC gel 10% by Artzi et al 7 case series reported promising efficacy and adequate safety. In the Millan-Cayetano et al 8 assessment of the OC patches, only 15 out of 25 patients reported significant efficacy and in the Berg on-Send ın study, 9…”
Section: Treatment Of Primary Axillary Hyperhidrosis With a Cream Formulation Of Oxybutynin Chloride 10%mentioning
confidence: 98%
“…Assessment in focal hyperhidrosis is controversial with a significant number of patients discontinuing treatment due to lack of efficacy or adverse effects. [6][7][8][9] Our objective was to evaluate the efficacy of a different formulation, a cream of oxybutynin chloride 10% prepared as a galenic formulation.…”
Section: Treatment Of Primary Axillary Hyperhidrosis With a Cream Formulation Of Oxybutynin Chloride 10%mentioning
confidence: 99%
See 1 more Smart Citation
“…[132] Use of transdermal patches led to mixed results. [145,146] Hence, studies were performed to investigate the topical application of oxybutynin for the treatment of primary focal hyperhidrosis in adults, adolescents and young adults. In adults with primary focal hyperhidrosis, a 10% oxybutynin gel appeared to be an effective and well-tolerated treatment in an RCT (NCT02973659).…”
Section: Modul Ator S Of the Cholinerg I C S Ys Temmentioning
confidence: 99%